2015
DOI: 10.1074/jbc.m114.620211
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors GATA4 and HNF4A Control Distinct Aspects of Intestinal Homeostasis in Conjunction with Transcription Factor CDX2

Abstract: Background: Different transcription factor combinations may control distinct or overlapping cellular functions. Results: Intestines lacking tissue-restricted CDX2 and broadly expressed GATA4 or HNF4A show unique defects. Conclusion: Combined with CDX2, GATA4 controls crypt cell replication, whereas HNF4A regulates enterocyte maturation and a cohort of functional enterocyte genes. Significance: Combinatorial mechanisms for intestine-specific gene regulation may apply generally to other tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 46 publications
12
66
0
Order By: Relevance
“…The CDX2 motif was strongly enriched in both groups of binding regions, but whereas Hindgutenriched sites were enriched in NANOG and SOX15 motifs, consistent with a role for SOX factors supporting endoderm development (Kanai-Azuma et al, 2002), Adult-enriched regions were most enriched in HNF4A motifs ( Fig. 2D, Table S1), consistent with the function of HNF4 in the mature intestine (Babeu et al, 2009;Cattin et al, 2009;San Roman et al, 2015;Stegmann et al, 2006). Examples of Hindgut-enriched target genes included the HOXB cluster genes ( Fig.…”
Section: Cdx2 Regulates Distinct Transcriptional Targets Across Humansupporting
confidence: 62%
See 1 more Smart Citation
“…The CDX2 motif was strongly enriched in both groups of binding regions, but whereas Hindgutenriched sites were enriched in NANOG and SOX15 motifs, consistent with a role for SOX factors supporting endoderm development (Kanai-Azuma et al, 2002), Adult-enriched regions were most enriched in HNF4A motifs ( Fig. 2D, Table S1), consistent with the function of HNF4 in the mature intestine (Babeu et al, 2009;Cattin et al, 2009;San Roman et al, 2015;Stegmann et al, 2006). Examples of Hindgut-enriched target genes included the HOXB cluster genes ( Fig.…”
Section: Cdx2 Regulates Distinct Transcriptional Targets Across Humansupporting
confidence: 62%
“…Low Input mRNA library kit (Clonetech SMARTer 634888). Adult RNA data were curated from GSE70766 and GSE98724 (San Roman et al, 2015;Saxena et al, 2017).…”
Section: Rna-seqmentioning
confidence: 99%
“…5G). These transcription factors have all been shown to play a role in intestinal development (Verzi et al, 2010;Beuling et al, 2012;Kerschner et al, 2014;Walker et al, 2014;Gosalia et al, 2015;San Roman et al, 2015;Yang et al, 2016), suggesting that Barrett's and OAC cells have reverted to a more primitive state where these factors are operational. For example, HNF4A, GATA6 and FOXA3 are all broadly expressed in the stomach, liver, pancreas and intestine during mouse embryogenesis but are absent from the oesophagus (Sherwood et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although the Y1H assay demonstrated that all three zebrafish Hnf4 members are capable of binding in3.4, we concentrated our efforts on understanding the function of Hnf4a because it is the most highly conserved Hnf4 family member (Supplemental Fig. S1G; Supplemental Table S10) and has well-documented roles in intestinal physiology (San Roman et al 2015). To that end, we generated hnf4a mutant zebrafish using the CRISPR/Cas9 system ( Fig.…”
Section: Resultsmentioning
confidence: 99%